2019
DOI: 10.1097/ijg.0000000000001108
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Corneal Endothelial Cell Loss After Trabeculectomy With Mitomycin C

Abstract: Purpose: To investigate factors associated with decreased corneal endothelial cell density (ECD) after trabeculectomy with mitomycin C (MMC). Methods: Retrospective review of consecutive glaucoma cases who underwent trabeculectomy with MMC. The types of glaucoma included were primary open-angle glaucoma, exfoliation glaucoma (XFG), neovascular glaucoma, and uveitic glaucoma (UG). The postoperative ECD changes compared with the preoperative ECD and risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 36 publications
3
17
0
2
Order By: Relevance
“…At present, the most common aetiology of corneal oedema is cataract surgery [6]. Filtering glaucoma surgery causes less cell loss than cataract surgery [7][8][9][10][11][12][13][14][15][16], but it may also cause significant cell loss, especially if combined with cataract surgery [12,14,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…At present, the most common aetiology of corneal oedema is cataract surgery [6]. Filtering glaucoma surgery causes less cell loss than cataract surgery [7][8][9][10][11][12][13][14][15][16], but it may also cause significant cell loss, especially if combined with cataract surgery [12,14,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The mean of ECD decreases at an average rate of approx. 0.6% per year for normal adults, whereas in patients underwent trabeculectomy were about 10% per year 9–11. The reasons rapid corneal endothelial cell loss due to trabeculectomy were toxic effects of mitomycin-C (MMC) or peripheral iridotomy 12,13.…”
Section: Discussionmentioning
confidence: 97%
“…The percentage of corneal endothelial cell density (ECD) loss after trabeculectomy ranged from 3.2% to 18.2% (Kim et al, 2016; Lee et al 2017; Arimura et al 2018; Hirooka et al, 2019). Furthermore, previous studies reported that the risk factors for corneal ECD loss after trabeculectomy are mitomycin C, older age, uveitic glaucoma and exfoliation glaucoma (Zarei et al 2015; Hirooka et al, 2019; Higashide et al; 2019). The present study aimed to evaluate the long‐term changes in corneal ECD loss after trabeculectomy and identify the risk factors for corneal ECD loss.…”
Section: Characteristics Total (N = 81) Trab‐alone (N = 65) Trab‐phaco (N = 16) P‐valuementioning
confidence: 99%